Real-time humidity measurement during sports activity using optical fibre sensing - He, C.; Korposh, S.; Hernandez, F. U.; Liu, L.; Correia, R.; Hayes-Gill, B. R.; Morgan, S. P. (Sensors, 2020)
An optical fibre sensor for monitoring relative humidity (RH) changes during exercise is demonstrated. The humidity sensor comprises a tip coating of poly (allylamine hydrochloride) (PAH)/silica nanoparticles (SiO2 NPs) deposited using the layer-by-layer technique. An uncoated fibre is employed to compensate for bending losses that are likely to occur during movement. A linear fit to the response of the sensing system to RH demonstrates a sensitivity of 3.02 mV/% (R2 = 0.96), hysteresis ± 1.17% RH when 11 bilayers of PAH/SiO2 NPs are coated on the tip of the fibre. The performance of two different textiles (100% cotton and 100% polyester) were tested in real-time relative humidity measurement for 10 healthy volunteers. The results demonstrate the moisture wicking properties of polyester in that the relative humidity dropped more rapidly after cessation of exercise compared to cotton. The approach has the potential to be used to monitor sports performance and by clothing developers for characterising different garment designs.